An Analytical Study in Klezmer Music: An Application of Prayer Chant and Klezmer Modes - Small, Rebecca (University of Ottawa (Canada), 2010)
This thesis studies the melodic elements of the klezmer music genre. First, the reader will observe the work of klezmer scholar Joshua Horowitz, who describes the basis of the klezmer genre as a set of four modes. As per convention, these modes are scale-based, but are additionally motivic in nature. Second, a similar modal system will be examined; that of the Synagogue Prayer Modes, which were identified primarily through the work of Jewish music scholars Abraham Zvi Idelsohn, and later, Baruch Joseph Cohon. Finally, a set of pieces found on the recording "Hassidic Tunes of Dancing and Rejoicing" will be analyzed both in terms of the klezmer and prayer modes. It is through this analytical process that the reader may determine how the motivic patterns within the modes influence the composition of a klezmer piece. This process will also highlight the link between the two sets of modes.
Keywords: Music.; Jewish Studies.